Dietary fibre and available carbohydrates in Finnish vegetables and fruits - Varo, Pertti; Laine, Raili; Veijalainen, Kirsti; Espo, Aila; Wetterhoff, Anne; Koivistoinen, Pekka (Agricultural and Food Science, 1984)
The dietary fibre and available carbohydrate contents of vegetables, fruits and berries commonly consumed in Finland were analysed using the Englyst total carbohydrate method. The tables give the composition of 73 fresh and processed vegetables and fruits. The estimated average daily intakes of carbohydrates received from this category of foods were: total soluble sugars 23.7 g, starch 30.6 g and dietary fibre 7.2 g (energy level 10 MJ).